Perencanaan Kampanye Syafrudin-Subadri Dalam Kontestasi Pilkada Kota Serang Tahun 2018 - Naufal Alka Muhammad; Hendra Hendra (Epistemik: Indonesian Journal of Social and Political Science, 2022)
The Serang City Election 2018 was enlivened by 3 pairs of candidates, one of whom was half incumbent who was the wife of the incumbent. With effective campaign planning, the pair Syafrudin-Subadri Usuludin was finally able to win from the half incumbent. the stages, methods, and factors that are in the planning of this campaign are interesting to study. In conducting this research, researchers took a reference focus from the theory, stages and campaign methods from Brian J. O'Day. The method used in this research is qualitative method. Data collection is done by interviewing informants, and from some secondary data such as field observations and documentation. The results of this study indicate that the pair Syafrudin and Subadri Usuludin along with the team carried out campaign stages in accordance with the six stages in conducting a campaign from Brian J. O'Day which consisted of conducting research, setting goals, setting target voters, building campaign messages, building relationship with voters, and campaign implementation. In addition there are several factors that make Syafrudin-Subadri Usuludin able to surpass the half incumbent such as, the saturation of the people of Serang City over the dynastic political practices in Serang City, the weakness of figures from the half incumbent and several other factors. Meanwhile, the stages of building campaign messages and building relations with voters were the hallmarks of this pair, individual approaches such as coffees and door to door method were decisive factors in the campaign of the pair Syafrudin and Subadri Usuludin in the 2018 Serang regional election.